The Effects of Perception of Fairness and Trust in Government on Voluntary Tax Compliance with Religiosity as The Moderating Variable: an Analysis - Manullang, Rafika Surya; Marfiana, Andri (Jurnal Pajak dan Keuangan Negara (PKN), 2024)
This study aims to determine the influence of perceptions of fairness and trust in the government on voluntary tax compliance with religiosity as a moderator variable. The object of this study is a private person who does independent work in the DKI Jakarta area. This study uses a quantitative approach with primary data in the form of 206 respondents' answers obtained from the questionnaire survey. Data analysis is using the Partial Least Square (PLS) model with the Structural Equation Modeling (SEM) method. The test results found that perceptions of fairness, trust in the government, and partial religiosity had a positive and significant influence on voluntary tax compliance. However, religiosity is not able to strengthen the relationship between perceptions of justice and trust in the government towards voluntary tax.